Emerging Trends in Sustainable Entrepreneurial Behavior: Bibliometric Data Insights - ABD RAHMAN, NURUL HAYANI; MOHAMED ISA, ZURAIDAH; ANUAR, AZYYATI (Information Management and Business Review, 2024)
The present study explores the current trends in sustainable entrepreneurial behavior to contribute fundamental knowledge for future academic research in the dynamic field of sustainable entrepreneurship. This study employs a bibliometric analysis using the Scopus database to identify significant changes and emerging topics in academic discourse about the selected keywords. By employing a systematic approach, one can attain a comprehensive understanding of the subject matter and establish a solid foundation for subsequent research. The analysis comprises a total of 666 articles obtained from Scopus. This study utilizes methodological tools like Microsoft Excel, Harzing’s Publish or Perish program, and VOS viewer. These tools were used to quantify and evaluate citation frequencies. This method enables the assessment of the academic output and influence exerted by document type, evolution of published studies, subject area, and prominent keywords. Nevertheless, there are several constraints associated with this study, including the omission of articles published after 2022 and a specific emphasis on English-language publications from 1991 to 2022. Notwithstanding these limitations, there has been a substantial and continuous academic emphasis on the study of sustainable entrepreneurial behavior. Future research should investigate sustainable behavior within the context of social entrepreneurship. The government and policymakers have the ability to significantly contribute to the creation of an ecosystem that promotes sustainable entrepreneurship and sustainable development.